The networked power of urban diplomacy in global governance - Cathryn Clüver Ashbrook (Revista CIDOB d'Afers Internacionals, 2023)
The network structures that have arisen out of globalisation could provide an alternative means of addressing major global challenges (climate change, mitigation of its effects or the prevention of pandemics). Cities increasingly consider themselves “actors motivated by interests” and they turn to urban diplomacy and interest-based networks to change the conversation – and, ultimately, the power structure – of multinational governance. Starting with a definition of what urban power is, this paper examines the rise of urban networks and their leverage of data to claim a more active role in the face of their nation-states, and on a global scale. Drawing on two brief case studies – the C40 network and Voluntary Local Reviews – it points to possible ways forward for urban networks of influence in the short term.